Efek Pemberian Pelepah Sawit Yang Difermentasi Dengan Prolinas Terhadap Karakteristik Rumen Sapi Perah PFH - Mardalena, Mardalena; Syarif, Suhessi; Akmal, Akmal (Fakultas Peternakan Universitas Jambi, 2016)
The study aimed to determine the effect of prolinas (pineapple skin probiotics) on the rumen fluid characteristic of dairy cows through in vitro method. A Completely Randomized Design with 4 treatments and 4 replications was applied. The treatments consist of A: oil palm fronds without fermentation (control), B: oil palm fronds fermented with prolinas of 2.5% dry matter (DM), C: oil palm fronds fermented with prolinas of 5% DM, D: oil palm fronds fermented with prolinas of 7.5% DM. Parameters measured were dry matter digestibility (DMD) and organic materials digestibility, N-NH3, rumen pH, concentration of volatile fatty acid in the rumen. The results showed that oil palm fronds fermented with prolinas with concentration of 5% DM was the best results in improving DMD and total VFA concentration in the rumen of dairy cows.